Risk perception of COVID-19 and its associated factors among Indigenous population in Malaysia - Ummi Mirza Baharudin; Zaleha Md Isa; Muhammad Hilmi Mahmud; Aniza Ismail; Faiz Daud; Siti Fairuz Abu Bakar (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indigenous people have a higher risk of experiencing the bad impact of COVID-19 once they are infected. This study aimed to identify the risk perception of COVID-19 among indigenous population and its associated factors. This is a cross-sectional study with psychometric evaluation of the Malay version of the risk perception of COVID-19 questionnaire. A total of 408 indigenous adults of the Semai tribe from a remote rural area of Pahang participated in the study. For psychometric evaluation, the item internal consistency reliability was 0.87, while the item separation was 2.57. Descriptively, mean age was 36-year-old (SD ±14), woman (60.8%), mean household income RM170 (SD ± RM355), had informal education (36%) and had job (92.9%). The cross-sectional finding highlighted that those who had job (adj.OR 4, CI: 1.118-14.374), had knowledge on COVID-19 (adj.OR 3.78, CI: 1.247-11.448), higher health literacy score (adj.OR 3.3, CI:1.262-8.852), higher trust on information (adj.OR 2.95, CI:1.071-8.109) and used more frequent information on COVID-19 (adj.OR 5.77, CI:1.228-27.063) had higher risk perception on COVID-19. Those did not agree to lift the government restriction has a protective factor in the level of risk perception on COVID-19 (OR 0.34, CI:0.131-0.879). The indigenous population in Malaysia has a high-risk perception of COVID-19; however, they need assistance complying with the government policy on preventive and control measures.